Immuogenetic factors influencing hypersensitivity to the anesthetic drugs - Kemoklidze, Tamar; Kamkamidze, George (Caucasus Journal of Health Sciences and Public Health, 2019)
Drug hypersensitivity reactions are an important public health problem due to their potential to cause lifethreatening anaphylaxis and rare severe cutaneous adverse reactions (SCAR). Drug hypersensitivity can be induced by immunologically mediated reactions (referred as drug allergies) as well as non-allergic direct mast cell-mediated drug reactions.